2022
DOI: 10.3390/infrastructures7070094
|View full text |Cite
|
Sign up to set email alerts
|

Structural Assessment Techniques for In-Service Crossarms in Power Distribution Networks

Abstract: Crossarms are widely used in power distribution and telecommunication sectors to support overhead cables. These structures are horizontally attached to the top of vertically erected utility poles and are essential elements in connecting overhead cables to the poles. Timber is the dominantly used material type for crossarms in the existing distribution networks. Nevertheless, there are alternative crossarms made from steel, composites, polymers, and even from concrete. This paper reviews the studies on the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Except for the visual inspection, advanced inspection techniques using aerial photographs have been developed for accurate inspection with the use of unmanned aerial vehicles. The condition assessment techniques for cross arms have been investigated and presented in the previous works of the authors [78]. The focus of this paper was mainly on condition monitoring and surveillance techniques for overhead cables, since overhead lines are a financially feasible and frequently-used option as carriers for electric energy.…”
Section: Condition Monitoring and Surveillance Techniques For Power D...mentioning
confidence: 99%
“…Except for the visual inspection, advanced inspection techniques using aerial photographs have been developed for accurate inspection with the use of unmanned aerial vehicles. The condition assessment techniques for cross arms have been investigated and presented in the previous works of the authors [78]. The focus of this paper was mainly on condition monitoring and surveillance techniques for overhead cables, since overhead lines are a financially feasible and frequently-used option as carriers for electric energy.…”
Section: Condition Monitoring and Surveillance Techniques For Power D...mentioning
confidence: 99%
“…In dry, hot, humid and windy conditions, sparks generated from a power distribution fault can ignite the biomass, initiating a fire. It is vital to monitor the structural health of power distribution systems to avoid potential faults, and power distribution infrastructure reaching the end of service life needs to be replaced [54][55][56][57]. A detailed investigation into the causes of the Black Saturday bushfires in Australia revealed that a power line brought down by high winds generated sparks that initiated the fire in the Kilmore East region, where 121 people were killed and approximately 100,000 ha burned in less than 12 h [2].…”
Section: Fire Weather Conditions and Bushfire Initiationmentioning
confidence: 99%